Exploring earth science - Thurber, Walter A.; Kilburn, Robert E.; Howell, Peter S.; Ames, Lee J. (Boston : Allyn and Bacon, 1975)
A textbook incorporating discussions of geology, astronomy, meteorology, and oceanography. Includes suggested experiments which need little supervision.
Includes index.
Bibliography: p. 493-494.
Keywords: Earth sciences; Earth sciences